Vladimir : a novel - Jonas, Julia May (Avid Reader Press, 2022)
"We are introduced to a popular English professor whose charismatic husband at the same small liberal arts college is under investigation for his inappropriate relationships with his former students. The couple have long had a mutual understanding when it comes to their extra-marital pursuits, but with these new allegations, life has become far less comfortable for them both. And when our narrator becomes increasingly infatuated with Vladimir, a celebrated, married young novelist who's just arrived on campus, their tinder box world comes dangerously close to exploding"--